Integrating Accounting and Logistics Strategy in Business Management - PYLYPENKOО. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
The effective business management in adverse economic conditions necessitates the search for ways for integrating business accounting with innovative approaches to business management of material resources, especially the logistics system. The need to integrate business accounting of material assets with the logistics system is substantiated by giving evidence of the complicating conditions for transportation of material assets in recent years, related, inter alia, with quarantine limitations. It is stressed that the requirements to logistics strategies are increasing along with growing transportation costs, diminishing deposits of natural resources, creating new product lines, setting new criteria for social, technological and environmental dimensions of business activities. It argued that when management staff overlook or ignore the potentials offered by logistics tools for management of material resources or when business accounting has no links with logistics, the impact of management on the purchase of material assets will be less effective. Theoretical foundations of the integration of business accounting and logistics strategy of transactions with material assets for the achievement of economic security of business activities are highlighted. The principal dimensions for such integration (organizational, methodological, control and protective) and their key components are discussed. Organizational and technical schemes are proposed, aimed at creating a business accounting system integrated with other management functions (planning, economic analysis, control), in order to enhance the orientation of business enterprise on the effectiveness of logistics activities and achievement of economic security. The main objectives of business accounting with respect to logistics costs are determined for the business enterprises implementing the abovementioned approach to organization of logistics management.